(untitled) (Faridpur Medical College Journal, 2013)
Sturge-weber syndrome is a disease characterized by capillary or cavernous haemangionsm (Port-wine stain) along the cutaneous division of Trigennial nerve. There is venous haemangionsm in subjacent leptomeninges, which may spread causing atrophy of cortex. The patient Md. Zobair Hossain, 11 years old boy, nondiabetic, nonhypertensive presented to us on 20.05.2011 with the complaints of repeated bleeding from a swelling over the outer aspect of right eye ball for 1 month, weakness of left half of body for 1 year and repeated convulsion for 7 years. Diagnosis was confirmed vy CT scan of brain. Through treatment is unsatisfactory, he was advised for laser theraphy for coetaneous lesion and anti-convulsant drug epilepsy. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16899 Faridpur Med. Coll. J. 2013;8(1): 44-45